Method for preparing multi-layer adhesive material

By performing surface treatment on the two surfaces of the filler-containing resin film and coating the thermosetting resin composition separately, the problems of insufficient dielectric properties, heat resistance and dip resistance of the bonding material between the multi-layer printed circuit boards in the prior art are solved, and a multi-layer bonding material with excellent properties is prepared.

CN115725245BActive Publication Date: 2025-04-25GUANGDONG SHENGYI SCI TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110996245.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-27
Publication Date
2025-04-25
Estimated Expiration
2041-08-27

AI Technical Summary

Technical Problem

It is difficult to prepare a multi-layer printed circuit board interlayer bonding material with excellent dielectric properties, heat resistance and dip solder resistance, especially in the case of filler PTFE substrates.

Method used

A dense and complete multi-layer bonding material was prepared by surface treatment and coating the thermosetting resin composition respectively on the two surfaces of the filler-containing resin film. The method includes coating the filler-containing resin on the substrate, drying and sintering, surface treatment and coating a thermosetting resin layer respectively to form a multi-layer structure.

Benefits of technology

The prepared multi-layer bonding material has high mechanical strength, and the copper clad plate exhibits excellent dielectric properties, heat resistance and immersion resistance. The dielectric constant is between 2.7 and 2.9, the dielectric loss is ≤0.002, and it is immersed in molten tin at 288°C for 5 minutes without bubbles or layering.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for preparing a multilayer adhesive material. The multilayer adhesive material comprises a first thermosetting resin layer, a filler-containing resin film and a second thermosetting resin layer which are arranged in sequence; the mass percentage of filler in the filler-containing resin film is 30-70%; the preparation method comprises the following steps: (1) coating a filler-containing resin on a substrate, drying, sintering and / or curing to obtain a filler-containing resin film attached to the substrate; (2) surface treating the side of the filler-containing resin film away from the substrate, coating a first thermosetting resin composition, drying to obtain a first thermosetting resin layer; (3) after providing a protective film on the first thermosetting resin layer, peeling off the substrate, surface treating the filler-containing resin film after peeling off the substrate, coating a second thermosetting resin composition, drying to obtain the multilayer adhesive material. The copper clad laminate containing the multilayer adhesive material has excellent dielectric properties, heat resistance and solder resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of communication materials, and in particular relates to a method for preparing a multilayer adhesive material. Background Art

[0002] In recent years, with the high performance, high functionality and networking of information communication equipment and computers, in order to transmit and process large-capacity information, the operating signals tend to be high-frequency, which puts forward new requirements for the materials of circuit substrates. With the development of high-frequency circuits towards multi-functions, the multi-layering of high-frequency circuits is becoming more and more common, and polytetrafluoroethylene (PTFE) printed circuit boards, as an important component of high-frequency circuits, also need to be multi-layered. However, since PTFE resin has almost no fluidity and adhesion, it is difficult to use as an adhesive material between layers of PTFE multilayer boards. Therefore, finding a suitable interlayer adhesive material for multilayer printed circuit substrates is of great significance to the development of the entire circuit substrate industry.

[0003] CN109760398A discloses a high-frequency copper-clad laminate fluorine-containing resin prepreg assembly method, including baking glass fiber cloth, preparing fluorine-containing resin impregnation liquid, immersing glass fiber cloth in fluorine-containing resin impregnation liquid, plasma activation, pressing and other steps; at the same time, after the prepreg and copper foil are pressed, they are immersed in the protective liquid, which further strengthens the adhesion between the prepreg and the copper foil; the protective liquid system has a reasonable composition, good compatibility between the components, and under the action of various molecular coordination, it is conducive to forming an interpenetrating network, ensuring the use strength of the copper-clad laminate, stable structure, and low water absorption. However, the heat resistance and solder resistance of the copper-clad laminate need to be further improved.

[0004] CN111171736A discloses a varnished cloth and a preparation method thereof, a copper-clad plate containing the same and its application. The varnished cloth comprises a PTFE bonding sheet and a soluble polytetrafluoroethylene (PFA) adhesive film layer covering both sides of the PTFE bonding sheet; wherein the components of the PTFE bonding sheet include an organic reinforcing material. The preparation method can be used for continuous roll-shaped rolling production, and the production process is simple and feasible. The preparation of the varnished cloth can be achieved by only one dipping and one coating. At the same time, the subsequent process of preparing the copper-clad foil can be formed by roller pressing to reduce the process cost. CN112538186A discloses an interlayer bonding sheet for multilayer boards and a preparation method thereof: the PTFE substrate is cleaned and dried with ethanol; then it is placed in a low-temperature plasma device for surface treatment; then a dielectric resin layer is respectively rolled on the upper and lower surfaces, and an interlayer bonding sheet for multilayer boards is obtained after curing. However, the preparation methods disclosed in the above content are not suitable for preparing PTFE interlayer bonding sheets containing fillers. The filler-containing PTFE substrate has low strength and may break during surface treatment and roller coating; the prepared multi-layer adhesive sheet has many defects and poor dielectric properties and heat resistance.

[0005] Therefore, developing a method for preparing an interlayer bonding material containing fillers while ensuring that the copper clad laminate has excellent dielectric properties, heat resistance and solder immersion resistance is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a multilayer adhesive material. The preparation method comprises performing surface treatment and coating a thermosetting resin composition on two surfaces of a filler-containing resin film, respectively, so that the obtained multilayer adhesive material is dense and complete, has high mechanical strength, and enables a copper clad laminate containing the multilayer adhesive material to have excellent dielectric properties, heat resistance, and resistance to dip soldering.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing a multi-layer adhesive material, wherein the multi-layer adhesive material comprises a first thermosetting resin layer, a filler-containing resin film and a second thermosetting resin layer which are arranged in sequence; the mass percentage of filler in the filler-containing resin film is 30-70%;

[0009] The preparation method comprises the following steps:

[0010] (1) coating a filler-containing resin on a substrate, drying, sintering and / or curing to obtain a filler-containing resin film adhered to the substrate;

[0011] (2) treating the surface of the filler-containing resin film obtained in step (1) on the side away from the substrate, coating the first thermosetting resin composition, and drying to obtain a first thermosetting resin layer;

[0012] (3) After providing a protective film on the first thermosetting resin layer obtained in step (2), the substrate is peeled off, the filler-containing resin film after the substrate is peeled off is surface treated, a second thermosetting resin composition is coated, and the film is dried to obtain the multilayer adhesive material.

[0013] Preferably, the protective film in step (3) can be selected from PET film, BOPP film, fluorine-containing resin film or release paper.

[0014] The mass percentage of filler in the filler-containing resin film is 30-70%, for example, it can be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70% and the like.

[0015] In the preparation method provided by the present invention, the filler-containing resin film has good mechanical strength due to the support of the substrate; by surface treating the two surfaces of the filler-containing resin film and coating the thermosetting resin composition respectively, the obtained multilayer adhesive material is dense and complete, so that the copper clad laminate has excellent dielectric properties, heat resistance and dip soldering resistance; when the filler-containing resin film is not supported by the substrate, the mechanical strength is poor, and by simultaneously surface treating the two surfaces of the filler-containing resin film and coating the thermosetting resin composition, the obtained multilayer adhesive material has more voids, resulting in the deterioration of the dielectric properties, heat resistance and dip soldering resistance of the copper clad laminate.

[0016] As a preferred technical solution of the present invention, the thermal expansion coefficient of the filler-containing resin film is less than 60ppm / °C, for example, it can be 16ppm / °C, 18ppm / °C, 20ppm / °C, 22ppm / °C, 24ppm / °C, 26ppm / °C, 28ppm / °C, 30ppm / °C, 32ppm / °C, 34ppm / °C, 36ppm / °C, 38ppm / °C, 40ppm / °C, 42ppm / °C, 44ppm / °C, 46ppm / °C, 48ppm / °C, 50ppm / °C, 52ppm / °C, 54ppm / °C, 56ppm / °C, 58ppm / °C, etc.

[0017] The coefficient of thermal expansion (CTE) test method in this article is: two filler-containing resin films to be tested are pressed into a plate, and the transverse CTE of the plate is tested according to the "TMA" experimental conditions in the IPC-TM-650 2.4.24.5 method.

[0018] Preferably, the filler-containing resin film includes any one of a filler-containing polytetrafluoroethylene (PTFE) film, a filler-containing polyimide (PI) film, a filler-containing liquid crystal polymer (LCP) film or a filler-containing polyetheretherketone (PEEK) film, or a combination of at least two thereof.

[0019] Preferably, the filler-containing resin film has a thickness of 20 to 200 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, etc.

[0020] Preferably, the filler in the filler-containing resin film includes any one of silicon dioxide, titanium dioxide, chopped glass fiber, aluminum oxide or hollow glass microspheres, or a combination of at least two of them.

[0021] Preferably, the average particle size of the filler is less than 15 μm, for example, it may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 14.5 μm, etc.

[0022] Preferably, the average particle size of the filler is less than 15 μm, and the maximum particle size is less than 80 μm. The particle size is tested by laser diffraction method using Malvern laser particle size analyzer, model MS3000.

[0023] Preferably, the filler-containing resin in step (1) comprises a combination of a filler and a resin, and the resin comprises any one or a combination of at least two of polytetrafluoroethylene (PTFE), polyimide (PI), liquid crystal polymer (LCP) or polyetheretherketone (PEEK).

[0024] Preferably, the filler-containing resin in step (1) is prepared by the following method, which comprises: uniformly mixing the resin, the filler and an optional solvent to obtain the filler-containing resin.

[0025] In the present invention, the resin can be purchased from the market, or synthesized by a preparation method known in the art.

[0026] Exemplarily, the resin is polytetrafluoroethylene, and the method for preparing the filler-containing resin includes: mixing polytetrafluoroethylene emulsion with a filler (such as silicon dioxide), and dispersing the mixture evenly to obtain the filler-containing resin.

[0027] Exemplarily, the resin is polyimide, and the method for preparing the filler-containing resin includes: reacting a diamine monomer with a dianhydride monomer to obtain a polyimide precursor; mixing the polyimide precursor with a filler and dispersing them uniformly to obtain the filler-containing resin.

[0028] Preferably, the substrate in step (1) comprises a polyimide film or a steel strip.

[0029] Preferably, the coating method in step (1) is scraping.

[0030] Preferably, the drying, sintering and / or curing in step (1) may include one or a combination of drying, sintering and curing.

[0031] Preferably, the drying temperature in step (1) is 80-120°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, etc.

[0032] Preferably, the drying time in step (1) is 0.5 to 1.5 h, for example, it can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, etc.

[0033] Preferably, the sintering or curing temperature in step (1) is independently 220-380°C, for example, it can be 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 330°C, 340°C, 342°C, 344°C, 346°C, 348°C, 350°C, 352°C, 354°C, 356°C, 358°C, 360°C, 362°C, 364°C, 366°C, 368°C, 370°C, 372°C, 374°C, 376°C, 378°C, 380°C, etc.

[0034] Preferably, the sintering or curing time in step (1) is independently 0.2 to 1 h, for example, 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, etc.

[0035] Preferably, the surface treatment methods in step (2) and step (3) each independently include any one of plasma treatment, sodium naphthalene solution treatment, sandblasting or arc treatment, or a combination of at least two thereof.

[0036] Preferably, the plasma treatment gas includes a mixture of argon and hydrogen.

[0037] Preferably, the volume ratio of argon to hydrogen is (3-5):1, for example, 3:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4:1, 4.2:1, 4.4:1, 4.6:1, 4.8:1, 5:1, etc.

[0038] Preferably, the voltage of the plasma treatment is 2000-4000 V, for example, it can be 2000 V, 2200 V, 2400 V, 2600 V, 2800 V, 3000 V, 3200 V, 3400 V, 3600 V, 3800 V, 4000 V, etc.

[0039] Preferably, the system vacuum degree of the plasma treatment is 400-600 Pa, for example, it may be 400 Pa, 420 Pa, 440 Pa, 460 Pa, 480 Pa, 500 Pa, 520 Pa, 540 Pa, 560 Pa, 580 Pa, 600 Pa, etc.

[0040] Preferably, the RF power of the plasma treatment is 2-4 kW, for example, 2kW, 2.2kW, 2.4kW, 2.6kW, 2.8kW, 3kW, 3.2kW, 3.4kW, 3.6kW, 3.8kW, 4kW, etc.

[0041] Preferably, the treatment time of the sodium naphthalene solution is 200 to 360 s, for example, it can be 200 s, 220 s, 240 s, 260 s, 280 s, 300 s, 320 s, 340 s, 360 s, etc.

[0042] Preferably, the concentration of the sodium naphthalene solution in the sodium naphthalene solution treatment is 0.5-1.2 mol / L, for example, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.1 mol / L, or 1.2 mol / L.

[0043] Preferably, the abrasive medium of the sandblasting comprises silicon dioxide.

[0044] Preferably, the average particle size of the silicon dioxide is 2 to 8 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc.

[0045] Preferably, the air pressure of the sandblasting treatment is 0.1-1 MPa, for example, it can be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1 MPa, etc.

[0046] Preferably, the first thermosetting resin composition and the second thermosetting resin composition independently include any one or a combination of at least two of epoxy resin, cyanate resin, polyphenylene ether, bismaleimide, polyimide, benzoxazine resin, polybutadiene, styrene-butadiene copolymer, multifunctional vinyl aromatic copolymer or ethylene-propylene rubber.

[0047] Preferably, the first thermosetting resin composition and the second thermosetting resin composition each independently further include any one of a crosslinking agent, an initiator, a filler or a flame retardant, or a combination of at least two thereof.

[0048] Preferably, the thickness of the first thermosetting resin layer and the second thermosetting resin layer is independently 20-100 μm, for example, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc.

[0049] Preferably, the coating methods in step (2) and step (3) are each independently roller coating.

[0050] Preferably, the drying temperature in step (2) and step (3) is independently 140-180°C, for example, it can be 140°C, 142°C, 144°C, 146°C, 148°C, 150°C, 152°C, 154°C, 156°C, 158°C, 160°C, 162°C, 164°C, 166°C, 168°C, 170°C, 172°C, 174°C, 176°C, 178°C, 180°C, etc.

[0051] Preferably, the drying time in step (2) and step (3) is independently 5 to 15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, etc.

[0052] Preferably, step (3) further comprises providing a protective film on the second thermosetting resin layer after the drying.

[0053] Preferably, the protective film is selected from PET film, BOPP film, fluorine-containing resin film or release paper.

[0054] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:

[0055] (1) coating a filler-containing resin on a substrate, drying at 80 to 120° C. for 0.5 to 1.5 h, and sintering at 340 to 380° C. for 0.2 to 1 h to obtain a filler-containing resin film adhered to the substrate;

[0056] (2) treating the side of the filler-containing resin film obtained in step (1) away from the substrate, coating the first thermosetting resin composition, and drying at 140 to 180° C. for 5 to 15 minutes to obtain a first thermosetting resin layer;

[0057] (3) After providing a protective film on the first thermosetting resin layer obtained in step (2), the substrate is peeled off, the filler-containing resin film after the substrate is peeled off is surface treated, a second thermosetting resin composition is coated, and the film is dried at 140 to 180° C. for 5 to 15 minutes to obtain a second thermosetting resin layer, and a protective film is provided on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0058] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] (1) The preparation method of the present invention performs surface treatment and coating of a thermosetting resin composition on two surfaces of a filler-containing resin film, thereby preparing a multilayer adhesive material having good mechanical strength and a dense and complete structure;

[0061] (2) The copper-clad laminate containing the multilayer adhesive material has excellent dielectric properties, a dielectric constant between 2.7 and 2.9, and a dielectric loss of ≤0.002; and the copper-clad laminate has good heat resistance and solder immersion resistance. When the copper-clad laminate is immersed in molten tin at 288° C. for 5 minutes, no bubbling or delamination occurs. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0063] The experimental materials and devices used in the embodiments and comparative examples of the present invention are as follows:

[0064] (1) Filler-containing resin A-1: ​​45 parts by weight of polytetrafluoroethylene emulsion (PTFE emulsion, particle size 0.25 μm, solid content 55%, D210C from Daikin Co., Ltd. of Japan) was added with 24.7 parts by weight of silicon dioxide (average particle size 10 μm, purchased from Jiangsu Lianrui), and stirred and mixed at high speed for 2 hours to obtain filler-containing resin A-1.

[0065] (2) Filler-containing resin A-2: 75 parts by weight of N-methylpyrrolidone (NMP) and 8.21 parts by weight of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) were mixed and dissolved to obtain a BAPP solution; the BAPP solution was placed in a water bath for cooling and nitrogen protection was passed through, and after 30 minutes, 5.943 parts by weight of biphenyltetracarboxylic dianhydride (BPDA) was added, and the mixture was stirred at high speed for 3 hours to obtain a polyimide resin precursor solution.

[0066] 45 parts by weight of the polyimide resin precursor solution were taken, and 20 parts by weight of silicon dioxide (average particle size 10 μm, purchased from Jiangsu Lianrui) was added, and the mixture was stirred and mixed at high speed for 2 hours to obtain filler-containing resin A-2.

[0067] (3) Thermosetting resin composition B-1: 70 parts by weight of methacrylic acid-terminated polyphenylene ether resin (MMA-PPE, SA9000 from SABIC) and 70 parts by weight of toluene were mixed and dissolved to obtain a functionalized polyphenylene ether resin solution; then 30 parts by weight of a crosslinking curing agent styrene-butadiene copolymer (R100 from Sartomer), 3 parts by weight of an initiator cumene peroxide (DCP), 15 parts by weight of a bromine flame retardant ethyl-bis(tetrabromophthalimide) (bromine content 67.2%, BT-93W from Albemarle) and 45 parts by weight of silica powder (average particle size 0.5 μm, SO-C2 from Admatechs of Japan) were added, and the mixture was stirred and mixed to obtain a thermosetting resin composition B-1.

[0068] (4) Thermosetting resin composition B-2: 30 parts by weight of ethylene propylene rubber (number average molecular weight 80,000 g / mol, Lion Chemical Company, USA), 40 parts by weight of polybutadiene (molecular weight 3,200 g / mol, purchased from Japan Soda Co., Ltd.), 30 parts by weight of silica (average particle size 10 μm, purchased from Jiangsu Lianrui) and 2 parts by weight of initiator benzoyl peroxide (Shanghai Kanglang Biotechnology Co., Ltd.) were dissolved in 50 parts by weight of xylene and mixed evenly to obtain a thermosetting resin composition B-2.

[0069] (5) Plasma generator: CD1200 plasma processor from EUROPLASMA, Belgium.

[0070] Example 1

[0071] This embodiment provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0072] (1) coating a filler-containing resin A-1 on a polyimide film (PI film), drying in an oven at 100° C. for 1 h, and sintering in an oven at 360° C. for 0.5 h to obtain a filler-containing resin film having a thickness of 20 μm attached to the substrate;

[0073] (2) Plasma treatment was performed on the side of the filler-containing resin film obtained in step (1) away from the substrate, with the voltage set to 3000 V, the system vacuum degree set to 500 Pa, and the radio frequency power set to 3 kW. After treatment for 200 s in a mixed gas of Ar and H2 with a volume ratio of 4:1, the film was coated with a thermosetting resin composition B-1 and dried at 160° C. for 10 min to obtain a first thermosetting resin layer with a thickness of 30 μm.

[0074] (3) After a polyester (PET) protective film is disposed on the first thermosetting resin layer obtained in step (2), the PI film is peeled off, and the filler-containing resin film after the PI film is peeled off is subjected to plasma treatment under the same treatment conditions as in step (2), and a thermosetting resin composition B-1 is coated and dried at 160° C. for 10 min to obtain a second thermosetting resin layer with a thickness of 30 μm, and a PET protective film is roll-pressed on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0075] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is as follows:

[0076] Two sheets of the multilayer adhesive material are stacked to a size of 250 mm × 250 mm, and 1OZ thick copper foil is covered on the upper and lower surfaces of the stacked resin layer for lamination. A pressure of about 400 PSI is applied, the maximum temperature is 210° C., and the retention time is 60 min to obtain the copper clad laminate.

[0077] Example 2

[0078] This embodiment provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0079] (1) coating the filler-containing resin A-1 on the PI film, drying in an oven at 100° C. for 1 h, and sintering in an oven at 360° C. for 0.5 h to obtain a filler-containing resin film with a thickness of 50 μm adhered to the substrate;

[0080] (2) treating the side of the filler-containing resin film obtained in step (1) away from the substrate with a naphthalene sodium solution, wherein the concentration of the naphthalene sodium solution is 0.8 mol / L, and after treating for 280 seconds, washing with ethanol and distilled water respectively, and drying; coating the thermosetting resin composition B-1, and drying at 160° C. for 10 minutes to obtain a first thermosetting resin layer with a thickness of 30 μm;

[0081] (3) After rolling a PET protective film on the first thermosetting resin layer obtained in step (2), the PI film is peeled off, and the filler-containing resin film after the PI film is peeled off is treated with a sodium naphthalene solution under the same treatment conditions as in step (2), and a thermosetting resin composition B-1 is coated and dried at 160° C. for 10 min to obtain a second thermosetting resin layer with a thickness of 30 μm. A PET protective film is rolled on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0082] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is as follows:

[0083] Two sheets of the multilayer adhesive material are stacked to a size of 250 mm × 250 mm, and 1OZ thick copper foil is covered on the upper and lower surfaces of the stacked resin layer for lamination. A pressure of about 400 PSI is applied, the maximum temperature is 210° C., and the retention time is 60 min to obtain the copper clad laminate.

[0084] Example 3

[0085] This embodiment provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0086] (1) coating the filler-containing resin A-1 on the PI film, drying in an oven at 100° C. for 1 h, and sintering in an oven at 360° C. for 0.5 h to obtain a filler-containing resin film with a thickness of 100 μm adhered to the substrate;

[0087] (2) sandblasting the side of the filler-containing resin film obtained in step (1) away from the substrate, wherein the grinding medium for sandblasting is silicon dioxide (average particle size 5 μm) and the air pressure for sandblasting is 0.5 MPa; coating the thermosetting resin composition B-1, and drying at 160° C. for 10 min to obtain a first thermosetting resin layer with a thickness of 30 μm;

[0088] (3) After rolling a PET protective film on the first thermosetting resin layer obtained in step (2), the PI film is peeled off, and the filler-containing resin film after the PI film is peeled off is sandblasted under the same treatment conditions as in step (2), and the thermosetting resin composition B-1 is coated and dried at 160°C for 10 minutes to obtain a second thermosetting resin layer with a thickness of 30 μm. The PET protective film is rolled on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0089] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is as follows:

[0090] Two sheets of the multilayer adhesive material are stacked to a size of 250 mm × 250 mm, and 1OZ thick copper foil is covered on the upper and lower surfaces of the stacked resin layer for lamination. A pressure of about 400 PSI is applied, the maximum temperature is 210° C., and the retention time is 60 min to obtain the copper clad laminate.

[0091] Example 4

[0092] This embodiment provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0093] (1) coating the filler-containing resin A-1 on the PI film, drying in an oven at 100° C. for 1 h, and sintering in an oven at 360° C. for 0.5 h to obtain a filler-containing resin film with a thickness of 200 μm adhered to the substrate;

[0094] (2) sandblasting the side of the filler-containing resin film obtained in step (1) away from the substrate, wherein the grinding medium for sandblasting is silicon dioxide (average particle size 5 μm) and the air pressure for sandblasting is 0.5 MPa; coating the thermosetting resin composition B-2, and drying at 160° C. for 10 min to obtain a first thermosetting resin layer with a thickness of 30 μm;

[0095] (3) After rolling a PET protective film on the first thermosetting resin layer obtained in step (2), the PI film is peeled off, and the filler-containing resin film after the PI film is peeled off is sandblasted under the same treatment conditions as in step (2), and a thermosetting resin composition B-2 is coated and dried at 160°C for 10 minutes to obtain a second thermosetting resin layer with a thickness of 30 μm. A PET protective film is rolled on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0096] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is as follows:

[0097] Two sheets of the multilayer adhesive material are stacked to a size of 250 mm × 250 mm, and 1OZ thick copper foil is covered on the upper and lower surfaces of the stacked resin layer for lamination. A pressure of about 400 PSI is applied, the maximum temperature is 210° C., and the retention time is 60 min to obtain the copper clad laminate.

[0098] Example 5

[0099] This embodiment provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0100] (1) coating a filler-containing resin A-2 on a polyimide film (PI film), drying in an oven at 100° C. for 1 h, and sintering in an oven at 360° C. for 0.5 h to obtain a filler-containing resin film having a thickness of 20 μm attached to the substrate;

[0101] (2) Plasma treatment was performed on the side of the filler-containing resin film obtained in step (1) away from the substrate, with the voltage set to 3000 V, the system vacuum degree set to 500 Pa, and the radio frequency power set to 3 kW, and the treatment was performed in a mixed gas of Ar and H2 with a volume ratio of 4:1 for 200 s, and the thermosetting resin composition B-1 was coated, and dried at 160° C. for 10 min to obtain a first thermosetting resin layer with a thickness of 30 μm;

[0102] (3) After rolling a PET protective film on the first thermosetting resin layer obtained in step (2), the PI film is peeled off, and the filler-containing resin film after the PI film is peeled off is subjected to plasma treatment. The treatment conditions are the same as those in step (2), and the thermosetting resin composition B-1 is coated and dried at 160°C for 10 minutes to obtain a second thermosetting resin layer with a thickness of 30 μm. The PET protective film is rolled on the second thermosetting resin layer to obtain the multilayer adhesive material.

[0103] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is as follows:

[0104] Two sheets of the multilayer adhesive material are stacked to a size of 250 mm × 250 mm, and 1OZ thick copper foil is covered on the upper and lower surfaces of the stacked resin layer for lamination. A pressure of about 400 PSI is applied, the maximum temperature is 210° C., and the retention time is 60 min to obtain the copper clad laminate.

[0105] Comparative Example 1

[0106] This comparative example provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0107] (1) coating a filler-containing resin A-1 on a clean PI film, drying in a vacuum oven at 100° C. for 1 h to remove moisture, baking at 260° C. for 1 h to remove the additive, baking at 350° C. for 10 min, and after cooling, peeling off the filler-containing resin film from the PI film to obtain a filler-containing resin film with a thickness of 20 μm;

[0108] (2) Plasma treatment was performed on both sides of the filler-containing resin film in step (1), with the voltage set to 3000 V, the system vacuum degree set to 500 Pa, and the radio frequency power set to 3 kW. After treatment for 200 s in a mixed gas of Ar and H2 with a volume ratio of 4:1, the double sides were coated with a thermosetting resin composition B-1 to obtain a single-layer thermosetting resin layer with a thickness of 30 μm. The layer was dried at 155°C for 5 min to obtain the multilayer adhesive material.

[0109] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is the same as that in Example 1.

[0110] Comparative Example 2

[0111] This comparative example provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0112] (1) coating a filler-containing resin A-1 on a clean and smooth PI film, drying in a vacuum oven at 100° C. for 1 h to remove moisture, drying at 260° C. for 1 h to remove the additive, baking at 350° C. for 10 min, and peeling the filler-containing resin film from the PI film after cooling to obtain a filler-containing resin film with a thickness of 50 μm;

[0113] (2) The filler-containing resin film of step (1) is treated with a sodium naphthalene solution on both sides, wherein the concentration of the sodium naphthalene solution is 0.8 mol / L. After treatment for 280 s, the film is taken out, washed with ethanol and distilled water respectively, dried, and coated with a thermosetting resin composition B-1 on both sides to obtain a thermosetting resin layer with a single layer thickness of 30 μm. The film is dried at 155° C. for 5 min to obtain the multilayer adhesive material.

[0114] The copper clad laminate is prepared from the multi-layer adhesive material, and the specific preparation method is the same as that in Example 2.

[0115] Comparative Example 3

[0116] This comparative example provides a method for preparing a multilayer adhesive material, and the specific steps are as follows:

[0117] (1) coating a filler-containing resin A-1 on a clean and smooth PI film, drying in a vacuum oven at 100° C. for 1 h to remove moisture, baking at 260° C. for 1 h to remove the additive, baking at 350° C. for 10 min, and after cooling, peeling off the filler-containing resin film from the PI film to obtain a filler-containing resin film with a thickness of 200 μm;

[0118] (2) The filler-containing resin film of step (1) is sandblasted on both sides, the abrasive medium of the sandblasting is silicon dioxide (average particle size 5 μm), the air pressure of the sandblasting is 0.5 MPa, and the thermosetting resin composition B-2 is coated on both sides to obtain a single-layer thermosetting resin layer with a thickness of 30 μm, and dried at 155°C for 5 minutes to obtain the multilayer adhesive material.

[0119] The copper clad laminate is prepared from the multilayer adhesive material, and the specific preparation method is the same as that of Example 4.

[0120] Performance Testing

[0121] 1. Dk and Df: tested by SPDR (splite post dielectric resonator) method, test conditions are A state, frequency is 10GHz;

[0122] 2. Solder immersion test: Immerse the copper clad laminate of 100mm×100mm in molten tin at 288℃ for 5 minutes, and observe visually whether there is delamination or bubbling on the copper clad laminate; if there is no delamination or bubbling, it is marked as "passed".

[0123] The specific test results are shown in Table 1:

[0124] Table 1

[0125] Dk(10GHz) Df(10GHz) Solder immersion resistance Example 1 2.85 0.0019 pass Example 2 2..80 0.0017 pass Example 3 2.75 0.0015 pass Example 4 2.7 0.0013 pass Example 5 2.9 0.0020 pass Comparative Example 1 2.95 0.0054 Layering Comparative Example 2 2.9 0.0047 Layering Comparative Example 3 2.8 0.0053 Layering

[0126] It can be seen from the above table that in a preparation method of a multilayer adhesive material provided by the present invention, a filler-containing resin film is adhered to a substrate, and the two surfaces are respectively surface-treated and coated with a thermosetting resin composition, so that the prepared multilayer adhesive material is dense and complete, and has good mechanical strength; the copper-clad laminate containing the multilayer adhesive material has excellent dielectric properties, good heat resistance and resistance to immersion soldering, and meets the performance requirements of copper-clad laminate materials in the field of high-frequency communications.

[0127] It can be seen from Examples 1-5 that the copper clad laminate containing the multilayer adhesive material obtained by the preparation method of the present invention has excellent dielectric properties, a dielectric constant between 2.7 and 2.9, and a dielectric loss ≤0.002; after being immersed in molten tin at 288°C for 5 minutes, the copper clad laminate does not experience bubbling or delamination.

[0128] By comparing Examples 1-5 with the comparative example, it can be seen that the method of simultaneously surface treating both sides of the filler-containing resin film and simultaneously coating both sides with a thermosetting resin has poor mechanical strength due to the absence of a supporting layer, and is prone to deformation or even breakage. The filler-containing resin film has many surface defects (such as voids and wrinkles), and is prone to residual impurities, resulting in poor dielectric properties of the copper clad laminate, with a dielectric loss of ≥0.0047. Delamination occurs after the copper clad laminate is immersed in molten tin at 288°C for 5 minutes.

[0129] In summary, the present invention adopts a method of surface treating and coating the two surfaces of the filler-containing resin film with a thermosetting resin composition respectively, and the prepared multilayer adhesive material has excellent performance, and the copper clad laminate containing the multilayer adhesive material has low dielectric loss, good heat resistance and resistance to immersion soldering.

[0130] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a multilayer adhesive material, characterized in that: The multilayer adhesive material comprises a first thermosetting resin layer, a filler-containing resin film and a second thermosetting resin layer arranged in sequence; the mass percentage of filler in the filler-containing resin film is 30-70%; The preparation method comprises the following steps: (1) coating a filler-containing resin on a substrate, drying, sintering and / or curing to obtain a filler-containing resin film adhered to the substrate; (2) treating the surface of the filler-containing resin film obtained in step (1) on the side away from the substrate, coating the first thermosetting resin composition, and drying to obtain a first thermosetting resin layer; (3) after providing a protective film on the first thermosetting resin layer obtained in step (2), the substrate is peeled off, the filler-containing resin film after the substrate is peeled off is subjected to surface treatment, a second thermosetting resin composition is coated, and the film is dried to obtain the multilayer adhesive material; The first thermosetting resin composition and the second thermosetting resin composition each independently include any one or a combination of at least two of epoxy resin, cyanate resin, polyphenylene ether, bismaleimide, polyimide, benzoxazine resin, polybutadiene, styrene-butadiene copolymer, multifunctional vinyl aromatic copolymer or ethylene-propylene rubber; The filler-containing resin film includes any one of a filler-containing polytetrafluoroethylene film, a filler-containing polyimide film, a filler-containing liquid crystal polymer film or a filler-containing polyetheretherketone film, or a combination of at least two of them.

2. The preparation method according to claim 1, characterized in that: The filler-containing resin film has a thermal expansion coefficient of less than 60 ppm / °C.

3. The preparation method according to claim 1, characterized in that: The thickness of the filler-containing resin film is 20-200 μm.

4. The preparation method according to claim 1, characterized in that: The filler in the filler-containing resin film includes any one of silicon dioxide, titanium dioxide, chopped glass fibers, aluminum oxide or hollow glass microspheres, or a combination of at least two of them.

5. The preparation method according to claim 1, characterized in that: The average particle size of the filler is less than 15 μm.

6. The preparation method according to claim 1, characterized in that: The substrate in step (1) comprises a polyimide film or a steel strip.

7. The preparation method according to claim 1, characterized in that: The coating method in step (1) is scraping.

8. The preparation method according to claim 1, characterized in that: The drying temperature in step (1) is 80-120°C.

9. The preparation method according to claim 1, characterized in that: The drying time in step (1) is 0.5 to 1.5 hours.

10. The preparation method according to claim 1, characterized in that: The sintering and / or curing temperatures in step (1) are independently 220-380°C.

11. The preparation method according to claim 1, characterized in that: The sintering and / or curing time in step (1) is independently 0.2 to 1 h.

12. The preparation method according to claim 1, characterized in that: The surface treatment methods in step (2) and step (3) independently include any one of plasma treatment, sodium naphthalene solution treatment, sandblasting or arc treatment, or a combination of at least two of them.

13. The preparation method according to claim 12, characterized in that: The gas for plasma treatment includes a mixed gas of argon and hydrogen.

14. The preparation method according to claim 13, characterized in that: The volume ratio of argon gas to hydrogen gas is (3-5):

1.

15. The preparation method according to claim 12, characterized in that: The voltage of the plasma treatment is 2000~4000 V.

16. The preparation method according to claim 12, characterized in that: The system vacuum degree of the plasma treatment is 400~600 Pa.

17. The preparation method according to claim 12, characterized in that: The radio frequency power of the plasma treatment is 2-4 kW.

18. The preparation method according to claim 12, characterized in that: The sodium naphthalene solution treatment time is 200 to 360 s.

19. The preparation method according to claim 12, characterized in that: The concentration of the sodium naphthalene solution in the sodium naphthalene solution treatment is 0.5-1.2 mol / L.

20. The preparation method according to claim 12, characterized in that: The abrasive medium for the sandblasting process includes silicon dioxide.

21. The preparation method according to claim 20, characterized in that: The average particle size of the silicon dioxide is 2-8 μm.

22. The preparation method according to claim 12, characterized in that: The air pressure of the sandblasting process is 0.1~1 MPa.

23. The preparation method according to claim 1, characterized in that: The first thermosetting resin composition and the second thermosetting resin composition each independently further include any one of a crosslinking agent, an initiator, a filler or a flame retardant, or a combination of at least two thereof.

24. The preparation method according to claim 1, characterized in that: The thickness of the first thermosetting resin layer and the second thermosetting resin layer are each independently 20 to 100 μm.

25. The preparation method according to claim 1, characterized in that: The coating methods in step (2) and step (3) are each independently roller coating.

26. The preparation method according to claim 1, characterized in that: The drying temperatures in step (2) and step (3) are each independently 140-180°C.

27. The preparation method according to claim 1, characterized in that: The drying time in step (2) and step (3) is independently 5 to 15 minutes.

28. The preparation method according to claim 1, characterized in that: Step (3) further comprises providing a protective film on the second thermosetting resin layer after the drying.

29. The preparation method according to claim 1, characterized in that: The preparation method specifically comprises the following steps: (1) coating a filler-containing resin on a substrate, drying at 80-120° C. for 0.5-1.5 h, and sintering and / or curing at 340-380° C. for 0.2-1 h to obtain a filler-containing resin film adhered to the substrate; (2) After surface treatment on the side of the filler-containing resin film obtained in step (1) away from the substrate, a first thermosetting resin composition is coated thereon, and the film is dried at 140 to 180° C. for 5 to 15 min to obtain a first thermosetting resin layer; (3) After providing a protective film on the first thermosetting resin layer obtained in step (2), the substrate is peeled off, the filler-containing resin film after the substrate is peeled off is subjected to surface treatment, a second thermosetting resin composition is coated, and the film is dried at 140-180° C. for 5-15 min to obtain a second thermosetting resin layer, and a protective film is provided on the second thermosetting resin layer to obtain the multilayer adhesive material.

Citation Information

Patent Citations

  • High-frequency copper-clad plate and fluorine-containing resin prepreg combination mode

    CN109760398A

  • Varnished cloth, preparation method thereof, copper-clad plate containing varnished cloth and application of varnished cloth

    CN111171736A

  • Inter-layer bonding sheet for multi-layer board and preparation method and application of inter-layer bonding sheet

    CN112538186A

  • Epoxy thermocuring adhesive film with initial viscosity and preparation method and application thereof

    CN111484806A